let x be the number, then: (x + 1) × 2 + 5 = x + 1 → 2x + 2 + 5 = x + 1 → 2x + 7 = x + 1 → 2x - x = 1 - 7 → x = -6 The number is -6. Checking: -6 +1 = -5; 5 × 2 = -10; -10 + 5 = -5 which is the same as -6 + 1 = -5.
23 + 2X = 5 2X = -18 X = -9
2 -> 9 = +79 -> 5 = -45 ->13 = +813 -> 10 = -310 -> 19 = +919 -> 17 = -2As you can see, every other time, the number is increased. It was originally increased by 7, then 8, then 9. So, the next number should be increased by 10 = 27
Let x = the numbernumber increased by 10 = x + 10
It will be 22348.
let x be the number, then: (x + 1) × 2 + 5 = x + 1 → 2x + 2 + 5 = x + 1 → 2x + 7 = x + 1 → 2x - x = 1 - 7 → x = -6 The number is -6. Checking: -6 +1 = -5; 5 × 2 = -10; -10 + 5 = -5 which is the same as -6 + 1 = -5.
23 + 2X = 5 2X = -18 X = -9
3x+30let x = "a number"(x+10) = "a number increased by 10"3(x+10) = "3 times a number increased by 10"Expand: 3x+30
x+8+x/5 = 20 x = 10
2 -> 9 = +79 -> 5 = -45 ->13 = +813 -> 10 = -310 -> 19 = +919 -> 17 = -2As you can see, every other time, the number is increased. It was originally increased by 7, then 8, then 9. So, the next number should be increased by 10 = 27
Let x = the numbernumber increased by 10 = x + 10
It will be 22348.
-5
To increase a number by a certain amount means to add that amount to the original number. In this case, to find 90 increased by 10, you would add 10 to 90. Therefore, 90 increased by 10 is equal to 100.
n+5
5p+10
X-5^2